Konseling karir bagi remaja pekerja tamatan SMA - Nurul Badriah; Ibrahim Guntur Nuary (Seminar Nasional Bimbingan dan Konseling Jambore Konseling 3)
The dynamic of juvenile life often cannot be separated from the background of their family. In some cases, a juvenile is forced being a good child and the other side should become breadwinner to fullfil their necessary of their family. This research examines how juvenile worker who graduated form senior high school is able to understand the concept of themselves. Through descrptive qualitative approach, understanding the concept of self-brand is described. The data were obtained by observation and interview with someone who graduated from senior high school in Losari, Cirebon. Hence, to investigate the career concept of worker juvenile of senior high school graduate is the alternatif from various choices of their life after graduation from senior high school.